Characteristic MR Imaging Findings of Cerebral Air Embolism Infarcts: A Case Series - Timpone, Vincent M.; Callen, Andrew L. (American Journal of Neuroradiology, 2024)
SUMMARY: Infarcts from cerebral air embolism are rare events with potentially catastrophic clinical consequences. The imaging features of cerebral air embolism are not well-defined in the literature. We report a novel constellation of MR imaging findings of cerebral arterial air emboli–induced infarcts in a series of 6 patients. Awareness of the more distinguishing MR imaging patterns of cerebral air embolism may help establish this diagnosis and facilitate implementation of timely treatment.ACAanterior cerebral arteryCAEcerebral air embolism